Gee whiz! Hodgson’s Hawk Cuckoo Hierococcyx fugax nisicolor in the Sisuwa and Sankhuwa river valleys, Makalu-Barun National Park buffer zone - Cox, Jack (Journal of Natural History Museum, 2008)
J. Nat. Hist. Mus. Vol.22, 2005 p.159-163